2020
DOI: 10.1007/s10346-020-01485-5
|View full text |Cite
|
Sign up to set email alerts
|

How robust are landslide susceptibility estimates?

Abstract: Much of contemporary landslide research is concerned with predicting and mapping susceptibility to slope failure. Many studies rely on generalised linear models with environmental predictors that are trained with data collected from within and outside of the margins of mapped landslides. Whether and how the performance of these models depends on sample size, location, or time remains largely untested. We address this question by exploring the sensitivity of a multivariate logistic regression—one of the most wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 63 publications
2
26
1
Order By: Relevance
“…This result is similar to that of Ozturk et al. (2021) who found that the accuracy of a logistic regression based susceptibility model saturated after 0.01% of the study region had failed and was used to train the model. The reason for this saturation likely relates to the averaging of landslide distributions.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This result is similar to that of Ozturk et al. (2021) who found that the accuracy of a logistic regression based susceptibility model saturated after 0.01% of the study region had failed and was used to train the model. The reason for this saturation likely relates to the averaging of landslide distributions.…”
Section: Discussionsupporting
confidence: 89%
“…This suggests that BLR-based landslide susceptibility modeling needs to move away from time-independence, which assumes landslide distributions are static, toward more dynamic or time-dependent modeling that can account for expected or unexpected temporal variations in landslide distributions, particularly following extreme events. This suggestion follows a growing number of similar recommendations in the literature for landslide susceptibility to be considered temporally dynamic (e.g., Gorsevski et al, 2006;Lombardo et al, 2020;Meusburger & Alewell, 2009;Ozturk et al, 2021).…”
Section: Impacts On Landslide Susceptibility Modelingmentioning
confidence: 76%
“…Although event‐based inventories include clear traces of the triggering mechanisms of landslides (von Specht et al., 2019), many other inventories, such as satellite‐based, lack crucial information linking a given landslide to a specific triggering mechanism (Behling et al., 2014). The missing information about triggering mechanisms decreases the efficacy of these inventories in landslide hazard analyses, as this could introduce biases, for instance, inadvertently using earthquake‐triggered landslides to assess landslide hazard for extreme rainfall (Ozturk et al., 2020). Hence, there is a need to identify triggers of landslides in exiting databases to make them usable in hazard models.…”
Section: Introductionmentioning
confidence: 99%
“…The base model includes only elevation, hillslope inclination, and total curvature along with the geology as landslide predictors (Table 1). These topographic features and geology are commonly ranked very high in landslide susceptibility studies (e.g., Schicker and Moon 2012;Althuwaynee et al 2014;Meyer et al 2014;Ozturk et al 2020) Additional topographic, land cover, or landuse related covariates potentially increase the performance of the base model, yet may also lead to overfitting. As we are primarily interested in how far incorporation of rainfall products increases predictive performance, we thus avoided including any other metrics.…”
Section: Methodsmentioning
confidence: 99%